Peran Orang Tua dalam Mendidik Anak Generasi Alpha di Era Digital - Dea, Cut; Wulandari, Wulandari (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2025)
Parents have an important role in educating their children. Each generation has different attitudes and personalities depending on changing times. The Alpha Generation is the generation born from 2010 to 2025. The life of the Alpha Generation cannot be separated from technological and digital developments. Technological and digital developments can be utilized by parents in educating the Alpha Generation. Alpha Generation children were born in an era of rapid technological progress. Even though times have changed, we still have to teach children character education, attitudes and norms that exist in life. Parents' limitations in understanding the use of technology means they need to take a real role in caring for and educating their children. Alpha generation children are much more literate in using technology than previous generations. Therefore, we as parents need to balance the use of technology with making physical activities fun and interesting for children. This article aims to analyze effective educational strategies in facing the challenges of the digital era. The research was conducted using qualitative methods that collected data through literature studies and interviews with education experts.